Ambiguity and professional accountability in physiotherapy practice. Acquired brain injury rehabilitation across health care levels - Irgens, Eirik Lind (European Journal of Physiotherapy, 2019)
At the time of this study, the Norwegian health care system was in the middle of the implementation of the Coordination reform, initiated in 2012 due to insufficient coordination and an increase in health care service expenditure. Earlier hospital discharge and increased municipal responsibilities for rehabilitation following acquired brain injuries (ABI) challenge the traditional rehabilitation trajectories and the physiotherapists’ efforts to enable ABI patients’ recovery. The aim of the study was to explore the physiotherapy practices in ABI rehabilitation trajectories by investigating how the involved physiotherapists experienced the process of transferring patients and coordinating physiotherapy services in the aftermath of the reform. The research adopted a social constructionist approach with a qualitative design. The focus was the physiotherapists’ perceptions, experiences and viewpoints regarding the redistribution of responsibilities following the coordination reform; potential practice variations in rehabilitation trajectories; and the communication of information and professional knowledge across health care levels. Interviews, field observations and collection of hospital discharge papers were conducted with specialist and primary health care physiotherapists involved in a total of 10 patients’ rehabilitation trajectories following ABI. The study was conducted in northern Norway. The three articles highlight the physiotherapists professional dilemmas related to service provision, perspectives on physiotherapy practice variations, and physiotherapists’ experience and viewpoints regarding the communication and development of physiotherapy knowledge in ABI rehabilitation trajectories. The study suggests that the physiotherapists experience dilemmas and conflicting values due to changes in the organization and provision of health care services in the aftermath of the Coordination reform, and emphasize how physiotherapy practice in ABI rehabilitation trajectories reside in complex social, cultural and ...